2015
DOI: 10.1016/j.reprotox.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A exposure inhibits germ cell nest breakdown by reducing apoptosis in cultured neonatal mouse ovaries

Abstract: Bisphenol A is a known endocrine disrupting chemical and reproductive toxicant. Previous studies indicate that in utero BPA exposure increases the percentage of germ cells in nests and decreases the percentage of primordial follicles. However, the mechanism by which BPA affects germ cell nest breakdown is unknown. Thus, we hypothesized that BPA inhibits germ cell nest breakdown by interfering with oxidative stress and apoptosis pathways. To test our hypothesis, ovaries from newborn mice were collected and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 49 publications
5
33
1
Order By: Relevance
“…In mice, in vitro studies of isolated neonatal ovaries indicate that high dose BPA exposure inhibited germ cell nest breakdown and accelerated primordial follicle recruitment compared to controls (99, 100), similar to some of the observations in in vivo studies. Specifically, BPA exposure decreased levels antigen KI-67 ( Ki67 ), tumor necrosis factor receptor superfamily member 6 ( Fas ), and caspases ( Casp3 and 8 ) (99, 100).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In mice, in vitro studies of isolated neonatal ovaries indicate that high dose BPA exposure inhibited germ cell nest breakdown and accelerated primordial follicle recruitment compared to controls (99, 100), similar to some of the observations in in vivo studies. Specifically, BPA exposure decreased levels antigen KI-67 ( Ki67 ), tumor necrosis factor receptor superfamily member 6 ( Fas ), and caspases ( Casp3 and 8 ) (99, 100).…”
Section: Resultssupporting
confidence: 76%
“…Specifically, BPA exposure decreased levels antigen KI-67 ( Ki67 ), tumor necrosis factor receptor superfamily member 6 ( Fas ), and caspases ( Casp3 and 8 ) (99, 100). Further, BPA increased levels of Bcl2 and factors related to the phosphatidylinositol 3-kinase/thymoma viral proto-oncogene (PI3K/Akt) signaling pathway (99, 100).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[70]). Zhou et al [71] revealed that bisphenol A exposure significantly inhibited germ cell nests breakdown by altering the expression of key ovarian apoptotic genes in cultured neonatal mouse ovaries. Interestingly, exposure of neonates to estrogenic compounds like bisphenol A significantly increases the number of multiple oocyte follicles (MOFs) in adult mice ovaries.…”
Section: Eacs With Estrogenic and Anti-estrogenic Propertiesmentioning
confidence: 99%
“…Importantly, the subtle meiotic changes induced during this fetal stage of oogenesis increase the frequency of chromosomally abnormal eggs and embryos in the adult (31). Exposure at a slightly later stage of development (late gestation in the rhesus monkey and immediately after birth in the mouse) disrupts the formation of ovarian follicles, leading to the generation of multioocyte follicles and unenclosed oocytes (32, 34, 35), altering viable follicle populations in the adult. Given these experimental data, the expectation for adult women exposed in utero would be, as follows: [1] an increase in pregnancy failure and birth defects, if exposure coincides with the onset of meiosis in the fetal ovary, and [2] a decreased ovarian reserve and potential shortening of the reproductive lifespan, if exposure occurs at the time of follicle formation.…”
Section: The Ovary: Vulnerability At Multiple Stagesmentioning
confidence: 99%